2017
DOI: 10.1002/ejlt.201700240
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions From Unsaturated Fatty Acids Concentrates of Carp Oil Using Chitosan, Gelatin, and Their Blends as Wall Materials

Abstract: This work aimed to study the development of food–grade nanoemulsions containing unsaturated fatty acids concentrates from carp oil, using chitosan, and gelatin as wall materials. The effects of chitosan:gelatin ratio, polymer concentration and homogenization time on the nanoemulsions characteristics were evaluated. Phase separation occurred when the chitosan:gelatin ratio was higher than 50:50. Nanoemulsions using proportion of chitosan over than 70% remained visually stable, with no phase separation, for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…Analysis of variance showed that wall type had a significant effect on the average diameter of the droplets. There are many reports that are consistent with the results of the present study (Esquerdo, Silva, Dotto, & Pinto, 2018;Hategekimana, Masamba, Ma, & Zhong, 2015). Table 4 shows the effect of wall type on emulsion properties.…”
Section: -3-2-particles Sizesupporting
confidence: 90%
“…Analysis of variance showed that wall type had a significant effect on the average diameter of the droplets. There are many reports that are consistent with the results of the present study (Esquerdo, Silva, Dotto, & Pinto, 2018;Hategekimana, Masamba, Ma, & Zhong, 2015). Table 4 shows the effect of wall type on emulsion properties.…”
Section: -3-2-particles Sizesupporting
confidence: 90%
“…For example, in cosmetics, plant-based oils are favored because they are generally non-hazardous and compatible with the skin. In a study by Esquerdo et al [ 115 ], fish oil was used to develop a supplement for human consumption due to its rich unsaturated fatty acid (UFA) content. In order to increase its solubility in water, the researchers proposed a nanoemulsion model.…”
Section: Nanoemulsions As a Topical Drug Delivery Systemmentioning
confidence: 99%
“…The oxidative stability of fish oil encapsulated in multiple NE with particle sizes 190−210 nm prepared using whey protein concentrate was enhanced, whereby key factors affecting the droplet size of NE and oxidative stability of fish oil were found to be whey protein concentrate concentration level and used antioxidant type (vitamin C and E) (Hwang et al 2017). Esquerdo et al (2018) designed food-grade NEs containing unsaturated fatty acids (UFA) concentrates from carp oil, using CS and gelatin as wall materials, in which these biopolymers provided high stability to the formulations and also behaved as good wall materials, whereby at 90:10 of CS:gelatin ratio the NE was in the acceptable range of the legislation after 7 days of storage, suggesting the increase of the physical and oxidative stability of UFA and such NEs could facilitate the addition of these lipophilic active ingredients in aqueous-based foods or beverages. Application of NE in combination with vacuum packing was found to maintain the polyunsaturated fatty acids content of sea bass (Dicentrarchus labrax) fillets stored at 22 °C, since NE s with hazelnut, canola, and soybean oils can be used as a preservative for fish and such NEs together with vacuum packing could prevent the lipid oxidation (Ozogul et al 2017).…”
Section: Nanoemulsions Encapsulating Fatty Acidsmentioning
confidence: 99%